Policies to Overcome Judicial Mafia Practices within the Supreme Court - Irhamy Tauhid (Faculty of Law, Universitas Lampung, 2020)
The practice of law enforcement in Indonesia until now is still surrounded by various problems that keep the law away from its main purpose to provide justice, certainty, and benefits to the community. this is due to the existence of judicial mafia practices that are difficult to eradicate. The study are focus What is the policy in the Supreme Court in eradicating judicial mafia practices within the court Why is there an obstacle in the role of the supreme court supervisory body in realizing the eradication of judicial mafia practices within the court? What is the ideal policy of the Supreme Court supervisory body in eradicating the judicial mafia This study uses a Normative and Empirical Juridical approach. Normative research is carried out on matters that are theoretical principles of law, whereas an empirical approach is carried out to study law in reality in the field. The results of the study found that one of the manifestations of criminal policy efforts in overcoming the practice of judicial mafia in the court environment by building the characteristics of the human resources of the judicial executing instrument that includes Judges and Clerks to become apparatus free from corruption through proven participation in socialization. , Technical guidance and also comparative studies to countries that have the determination to eradicate corruption, conduct Coordination and Supervision Consultation at the Regional Level and Formation of Liaison and Assistance Team, There is an obstacle in the role of the Supreme Court supervisory body in realizing eradication of judicial mafia practices in the court environment due to by the Weak Sectoral Law Enforcement Supervisory Body in each of the Judicial Agencies, Government policies in eradicating judicial corruption are often counterproductive and the ideal Policy of the Court Supervisory Agency great in eradicating the judicial mafia is carried out by means of penal and non-penal namely namely by using criminal law facilities to punish the perpetrators involved in the practice of judicial mafia starting from the judge who hears the case to the court clerk. As for the suggestions that can be conveyed in this study, it is better for the Supreme Court to immediately improve its supervision of the actions of the judicial mafia in the court, especially in conducting law enforcement that is not selective; and It is better that judges are not easily persuaded by bribes to handle a case and also maintain the dignity of the judge in hearing the case being handled.